Language challenges and coping among international doctoral students: Perspectives from students, staff, and the institution - Gao, Bing (Journal of International Students, 2026)
This study examines international doctoral students’ language challenges during acculturation in the U.S. Specifically, it explores how students described their challenges and coping strategies and how the University and its staff influenced their language experiences. Fourteen students and three staff members from a midwestern U.S. university participated. Data were collected through a Qualtrics survey and semistructured interviews. Using Núñez’s (2014) multilevel model of intersectionality, this study groups students into self-identified English-dominant and less-English-dominant groups. It identifies the distinct language challenges they face and the coping strategies they employ. The findings also show that although university services and staff support facilitated students’ language adjustment, limited student engagement with some services revealed structural issues in their organization and implementation. The study concludes with recommendations for improving educational support and offers directions for future research.